Optimization of Turjawali Unit Samapta in the Prevention of Klitih in Klaten Resort Police - Fakhri, Raihan (Advances in Police Science Research Journal, 2024)
Klitih is the activity of individuals who go out at night without purpose. However, the term currently has a negative connotation due to the actions of teenagers or students involving road violence in various situations. In order to prevent klitih and strengthen the performance of harkamtibmas, Klaten Police need to optimize the Samapta field in terms of patrols as a form of prevention of klitih action. The purpose of this study is to describe the work systematics of the Turjawali Unit of the Klaten Police Samapta Unit and describe the quality of personnel of the Klaten Police Samapta Unit Turjawali Unit. Conceptual literature uses several theories, namely Management theory, SWOT theory, and Competency theory. While the concepts used include the concept of Samapta, the concept of Patrol, the concept of Klitih, the concept of Optimization. The research method used is a qualitative method with the type of case study research and field research. Data sources include primary and secondary through observation, interviews, and documentation studies. Data validity was obtained using data triangulation. The research location is the Klaten Police jurisdiction. The findings during the research are (1) the systematic work of the Turjawali Unit of the Klaten Police Samapta Unit is not optimal due to planning, organizing, implementing, supervising and the 4M elements (man, money, machine & material, methods) which are not in line with Perbaharkam No. 1 of 2017 concerning patrols and (2) the quality of personnel is not optimal due to the lack of abilities, skills, and attitudes of the personnel. The conclusions of the study are (1) the implementation of the patrols of the Turjawali Unit of the Klaten Police Samapta Unit is not optimal because the stages of planning, organizing, implementing, and supervising as well as the elements of 4M (man, money, machine & material, methods) are not in line with Perbaharkam No. 1 of 2017 concerning patrols so that the implementation is less than optimal and (2) the quality of personnel who are not supported by qualified abilities and skills and the lack of attitude of the personnel.